Pengaruh Social Media Marketing terhadap Minat Berkunjung Wisatawan di Kota Bandung Melalui Nilai yang Dipersepsikan - Alvin Satria Nugraha; Tania Adialita (Penerbit Goodwood, 2021)
Purpose: This research aimed to analyze the effect of social media marketing (SMM) on visit intention towards tourist attractions in Bandung, mediated by their perceived value. Research methodology: The research approach used a quantitative method using a questionnaire that involved 90 followers of Instagram account related to Bandung tourist destinations posts. Results: Using SPSS Ver.22, the findings claimed that the SMM has a positive effect on perceived value simultaneously. However, only one dimension of SMM, which is communication, has a partial effect on visit intention. Furthermore, the followers’ perceived value successfully mediates SMM on the visit intention. Limitations: This research is limited merely to utilizing one social media platform (Instagram account) related to Bandung's tourist attraction. Hence, further research covering the utilization of other social media platforms related to tourist attraction in various locations in Indonesia is needed to obtain comprehensive findings. Contribution: This research contributes to the advancement of marketing management to help stakeholders in the tourism industry determine SMM strategy using the Instagram account that can be utilized as a platform to shape positive perceived value and drive tourist visit intention.